Inteligencia intrapersonal y resiliencia en estudiantes de Ingeniería Civil de la Universidad Peruana Los Andes de Huancayo - Aliaga Contreras, Aron Jhonatan (2023)
The objective of the research was to determine the relationship between intrapersonal intelligence and resilience in students of the professional school of Civil Engineering of the Universidad Peruana Los Andes. The study with a quantitative approach, basic type, correlational level and descriptive correlational design, had 323 students as a sample; As instruments, the Bar-On ICE Intrapersonal Intelligence Test adapted by Ugarriza (2001) and the Wagnild and Young Resilience Scale (RE) adapted by Novella (2002) were applied. The results determined a positive correlation (.564) between intrapersonal intelligence and resilience; Furthermore, bilateral significance (.000) was evident between both variables; On the other hand, 55.73% of the students reached a high level of intrapersonal intelligence and 61.92% achieved a medium level of resilience. It was concluded that there is a statistically significant moderate correlation in the population between intrapersonal intelligence and resilience in the students of the Professional School of Civil Engineering of the Universidad Peruana Los Andes de Huancayo.